(3NWHI GdHMQ GdRNGQ dePGgH YdeGA GdGeUGQs
(3ChdgG (B:s
(3GdMeO ddg hSdGe Ydi YHGOg GdPjf GUWai GeG HYO aEf GdYGde UGQ eOjOkG bYjQkG ZhQg s
(3BNQgG (B:s
(3aGdaQbI GdfGLjI MjfFP ef OGf HGYJbGOge GdOjfi UOQ gPg GdaQb GdeYJRdI hZjQge hgh GdYOd hGdJhMjO Je cJGH Gdedd hGdfMd s
(3Vef eLehY , JQJjHgG (B: 2s
(3HgG fXGe GdJYbjHIs
(3hLYdg Ydi eSGFd hajg cJGH Gdedd hGdfMd ddeUfas
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3eJaQbGJs